PENGGUNAAN DEIKSIS DALAM BERITA UTAMA RIAU POS - Febry Eka Syafitri; Charlina '; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study has two formulation problems, among others (1) what kind of deixis in the headlines of Riau Pos edition January 2017?, (2) what are the meaning of deixis in the headlines of Riau Pos edition in January 2017? Based on the problem statement this study investigates (1) To identify of deixis types in headlines Riau Pos edition in January 2017 edition (2) To identify the meaning of deixis the headlines of Riau Pos, 2017edition. The research method used is a qualitative method that was describe descriptive data. The collection of datas used are literature study technique. Based on the data analysis which has been done was found 433 deixis by dividing (a) deixis persona 223 Data with the first deixis persona 64 datas that are “saya” 19 datas, “kami” 32 datas, “kita” 13 datas, the second deixis persona data that is in words ”Anda”, third person deixis 158 datas containing “dia” 41 datas, “ia” 8 datas, “-nya” 83 datas, “beliau” 25 datas. (B) Deixis place 26 datas with the detail word “disini” 5 Datas, “disitu” 2 records, “disana” 6 datas, demonstrative this 2 datas, demonstrative that 6 datas, “datang” 5 datas (c) deixis time 65 datas indicating the time at 21 Datas that aresekarang 6 datas, “kini” 5 datas, saat ini” 10 datas, the demonstrative “ini” 10 datas, in the past 25 datas that are “kemarin” 12 datas, “lalu” 13 of datas, the futuretime 4 records that are “besok” 1 data, “nanti” 3 datas, (d) deixis discourse 111 datas mentioning “anafora” discourse 100 datas, the “katafora” discourse 11datas, and (e) social deixis 8 datas with the details of the use of euphemisms 1 record, the mention of the title 7 Datas.Keywords: Deixis, headlines, riau pos